2014
DOI: 10.4161/15592294.2014.983381
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the catalytic domains of multiple JmjC oxygenases using peptide substrates

Abstract: These authors contributed equally to this work.Keywords: demethylation, Epigenetics, histone, methyllysine, JmjC histone demethylase, 2OG oxygenases The JmjC-domain-containing 2-oxoglutarate-dependent oxygenases catalyze protein hydroxylation and N emethyllysine demethylation via hydroxylation. A subgroup of this family, the JmjC lysine demethylases (JmjC KDMs) are involved in histone modifications at multiple sites. There are conflicting reports as to the substrate selectivity of some JmjC oxygenases with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 43 publications
(88 reference statements)
5
63
0
Order By: Relevance
“…The structure of the catalytic domain of the human 2-oxoglutarate dependent nonheme iron oxygenase N e -methyllysine demethylase (KDM4A) is characterized by an eight-residue linear Tyr/Trp chain [5-Å ET cutoff, PDB ID 4W2V (45)]. The enzyme is believed to catalyze lysine demethylation in a hydroxylation/demthylation sequence involving an Fe IV (O) intermediate (45). The central portion of the Tyr/Trp chain (Tyr275 and Trp187) passes ∼9 Å from the active site Fe center and terminates near surface exposed residues (Tyr273 and Trp181; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the catalytic domain of the human 2-oxoglutarate dependent nonheme iron oxygenase N e -methyllysine demethylase (KDM4A) is characterized by an eight-residue linear Tyr/Trp chain [5-Å ET cutoff, PDB ID 4W2V (45)]. The enzyme is believed to catalyze lysine demethylation in a hydroxylation/demthylation sequence involving an Fe IV (O) intermediate (45). The central portion of the Tyr/Trp chain (Tyr275 and Trp187) passes ∼9 Å from the active site Fe center and terminates near surface exposed residues (Tyr273 and Trp181; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast with the strict specificity of Jmjd3 and Utx, some members of other JmjC sub-families have a broader substrate range. However, they have little if any demethylase activity on H3K27Me3, with the possible exception of Kdm4 family members [36]. While the JmjC protein Jhdm1d (encoded by Kdm7) also demethylates H3K27Me2, and has been reported to associate with Jmjd3 [18], it has not been shown to act on its own on H3K27Me3.…”
Section: H3 K27 Methylation and Demethylationmentioning
confidence: 99%
“…It was recently reported that additional JmjC-family demethylases, including members of the Kdm4 family, exhibit H3K27Me3 demethylase activity [36], and future studies will examine their impact of H3K27Me3 in vivo . Of note, such functional redundancy would be gene specific, as H3K27Me3 removal at specific promoters (e.g.…”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…Relevant targets of JmjC histone demethylases (Loenarz & Schofield, 2008) were measured in whole‐worm extracts across multiple stages of development, and included H3K4me3, H3K27me3, H3K9me3, and H3K36me3. The latter three sites are demethylated by JMJD‐2/JMJD2A (Williams et al ., 2014). Analysis at this gross level, however, revealed no significant disruption in the methylation patterns of these four targets (Fig.…”
Section: Resultsmentioning
confidence: 99%